Synthesis and optimization of Fe2O3 nanofibers for chromate adsorption from contaminated water sources. (February 2016) - Nalbandian, Michael J.; Zhang, Miluo; Sanchez, Joel; Choa, Yong-Ho; Nam, Jin; Cwiertny, David M.; Myung, Nosang V.
Abstract: In this work, α-Fe2 O3 nanofibers were synthesized via electrospinning and characterized to observe optimal morphological and dimensional properties towards chromate removal. The Fe2 O3 nanofiber samples were tested in aqueous solutions containing chromate ( CrO 4 2 − ) to analyze their adsorption capabilities and compare them with commercially-available Fe2 O3 nanoparticles. Synthesized Fe2 O3 nanofibers were observed with a variety of different average diameters, ranging from 23 to 63 nm, while having a constant average grain size at 34 nm, point zero charge at pH 7.1, and band gap at 2.2 eV. BET analysis showed an increase in specific surface area with decreasing average diameter, from 7.2 to 59.2 m 2 /g, due to the increased surface area-to-volume ratio with decreasing nanofiber size. Based on CrO 4 − 2 adsorption isotherms at pH 6, adsorption capacity of the Fe2 O3 nanofibers increased with decreasing diameter, with the 23 nm sized nanofibers having an adsorption capacity of 90.9 mg/g, outperforming the commercially-available Fe2 O3 nanoparticles by nearly 2-fold. Additionally, adsorption kinetics was also analyzed, increasing with decreasing nanofiber diameter. The enhanced performance of the nanofiber is suggested to be caused solely due to the increased surface area, in part by its size and morphology. Electrospun Fe2 O3 nanofibers provide a promising solution for effective heavy metal removal through nanotechnology-integrated treatment systems. Highlights: We synthesized tunable Fe2 O3 nanofibers via electrospinning. We examined property changes as a function of nanofiber diameter. Adsorption isotherm and kinetic studies toward chromate removal were conducted. The d = 23 nm Fe2 O3 nanofibers showed optimal chromate adsorption performance. The enhanced performance was associated with increased specific surface area.